A Review of Methods for the Removal of Endocrine-Disrupting Compounds with a Focus on Oestrogens and Pharmaceuticals Found in Wastewater - Jolanta Latosińska; Agnieszka Grdulska (Applied Sciences, 2025)
Steroid hormones are micropollutants that contaminate water worldwide and have significant impacts on human health and the environment, even at very low concentrations. The aim of this article is to provide an overview of technologies for the removal of endocrine-disrupting compounds with a focus on oestrogens (estrone E1, 17β-oestradiol E2, estriol E3), the synthetic oestrogen (17α-ethinylestradiol EE2 and bisphenol A BPA), and pharmaceuticals found in wastewater. Hormonal and pharmaceutical contaminants are mostly persistent organic compounds that cannot be easily removed using conventional wastewater treatment processes. For this reason, researchers have tried to develop more efficient tertiary wastewater treatment technologies to reduce micropollutant concentrations in wastewater. This review covers the following processes: Advanced oxidation, nanofiltration, ultrasound, electro-Fenton processes, electrolysis, adsorption, ozonation, photolysis, photocatalysis, ultrafiltration, and electrocoagulation. Attention was paid to the effectiveness of the processes in terms of eliminating hormones and pharmaceuticals from wastewater, as well as on economic and environmental aspects. The combination of different processes can be a promising treatment scheme for retaining and degrading hormonal and pharmaceutical compounds from wastewater. With hybrid technologies, the advantages of the methods are combined to maximise the removal of pollutants. However, optimal methods of wastewater treatment depend on the quality and quantity of the wastewater, as well as the residual hormonal and pharmaceutical compounds and their hazardous effects.